2009
DOI: 10.1136/bjo.2009.164913
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis following open globe injury

Abstract: Laceration was associatied with a significantly higher risk of endophthalmitis for open globe injuries. Early primary repair, intraocular tissue prolapse and self-sealing of wounds were independent protective factors against the development of endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
99
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 23 publications
10
99
2
3
Order By: Relevance
“…5,14 The reported incidence rate of endophthalmitis following open-globe injury ranges from 0 to 16.5% (Table 1), with evidence of a general decline over the past 70 years. 4,6,12,[14][15][16][17][18][19][20][21][22][23][24] Prophylactic factors in the setting of trauma include primary wound repair within 24 h, lack of tissue prolapse into wounds and self-sealing wounds. 20 In a report from the American Trauma Registry, the incidence of endophthalmitis did not significantly differ among various types of foreign bodies.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,14 The reported incidence rate of endophthalmitis following open-globe injury ranges from 0 to 16.5% (Table 1), with evidence of a general decline over the past 70 years. 4,6,12,[14][15][16][17][18][19][20][21][22][23][24] Prophylactic factors in the setting of trauma include primary wound repair within 24 h, lack of tissue prolapse into wounds and self-sealing wounds. 20 In a report from the American Trauma Registry, the incidence of endophthalmitis did not significantly differ among various types of foreign bodies.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…6,12,[14][15][16][17][18][19][20][21][22][23][24] (2) Delay in wound closure of 424 hFthere is a fourfold increase in the infection rate when there was a delay of 424 h. 6 (3) Injury in a rural settingFthe incidence of endophthalmitis was reported to be higher when penetrating injury occurred in a rural setting, which was attributed to a higher incidence of soil contamination.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%
“…Before instituting antifungal treatment, distinguishing fungal from bacterial post-traumatic endophthalmitis is important because the treatments are different and prophylactic antifungal treatment can be toxic both systemically or locally. [2][3][4] A clinical feature that suggests fungal infection is a delayed onset of inflammation after injury. [2][3][4] Literature search has reported that all post-traumatic cases of fungal endophthalmitis became symptomatic between the first and fifth weeks after injury, with minimal discomfort to the patient.…”
Section: Sir Post-traumatic Endophthalmitismentioning
confidence: 99%
“…[2][3][4] A clinical feature that suggests fungal infection is a delayed onset of inflammation after injury. [2][3][4] Literature search has reported that all post-traumatic cases of fungal endophthalmitis became symptomatic between the first and fifth weeks after injury, with minimal discomfort to the patient. 3,4 In the absence of microbiological diagnosis, clinical signs suggesting infection include slow indolent smouldering intraocular inflammation associated with a relatively quiet eye, which may or may not be associated with the presence of an inflammatory mass in the vitreous or anterior chamber that is described as a 'fungal ball', or white vitreous 'snowball', or 'string of pearls'.…”
Section: Sir Post-traumatic Endophthalmitismentioning
confidence: 99%
See 1 more Smart Citation